VALUASI EKONOMI SUMBERDAYA TERUMBU KARANG DI PULAU SAUGI, KABUPATEN PANGKEP, INDONESIA - Wahyudin, Wahyudin; Adhawati, Sri Suro; Baso, Aris (Department of Socio-economic Fisheries, Marine Science and Fisheries Faculty, Universitas Maritim Raja Ali Haji, 2021)
Degradation of coral reef is rapidly increasing every year lead to negative impact of decreasing the value of coral reefs its self. In the present study aims to evaluate the economic value of coral reefs especially for use value, optional value, and existence value. The study was carried out from December 2011 to January 2012 in Saugi Island, Pangkep regency, Indonesia. The study site was choosen as purposively with considerate that majority of fishermen catch fish near the island. Field observation was collected the sampling used the questionnaire, 46 fishermen was interviewed. The result showed that IDR 3 million year-1, IDR 1.1 million year-1, IDR 13 million year-1for use value, optional value, and existing value of coral reefs, respectively. The total economic value (TEV) of coral reef in Saugi Island was IDR 3.02 Billion year-1or IDR 362 million ha-1year-1. The amount of economic value is important for decision-maker to act or make policy for coral reef resources management in the future.